Mental health issues impacting pharmacists during COVID-19 - Ali Elbeddini; Cindy Xin Wen; Yasamin Tayefehchamani; Anthony To (Taylor & Francis Group, 2020)
The coronavirus disease 2019 (COVID-19) impact on the mental health of healthcare workers is extremely detrimental. It is imperative that the psychological health of all healthcare workers be protected. However, an often overlooked member of the healthcare frontline is the pharmacist. Pharmacists provide many types of essential services during the pandemic, which often cannot be done from a remote location. Being frontline healthcare workers, pharmacists have experienced an increase in the number of patients seen, the amount of screening and triage being done, the amount of COVID-19 information being delivered, the number of medication shortages, and the amount of workplace harassment taking place. These activities increase the amount of stress, burden, and frustration felt by pharmacists have a negative impact on their mental health and well-being. This article seeks to address the specific implications of COVID-19 on the mental health of pharmacists.